Effect of Aviation Turbine Fuel Exposure on Interlaminar and Inplane Shear Properties of Glass Fiber Reinforced Epoxy Composite - Shrivastava, S.M.; Ramarao, G; Buragohain, Manoj Kumar; Selvaraj, N (Defence Science Journal, 2022)
This study investigated the effect of aviation turbine fuel exposure on interlaminar and in-plane shear properties of E-glass/epoxy composite. The two types of test specimens, namely bare and resin-coated specimens with varying thicknesses as per the ASTM standard, were made out of E-glass/epoxy composite to evaluate their interlaminar and in-plane shear properties. These all types of specimens were immersed inside the aviation turbine fuel for two months and then afterward their effect on the reduction of mechanical properties like interlaminar and in-plane shear tests properties were experimentally investigated. Test results show that ATF fuel exposure has reduced the interlaminar shear strength by 10.04 %, 7.83 %, and 6.01 % for bare, with 0.1 mm and 0.2 mm resin coating, respectively. Similarly, in-plane shear strength was reduced by 14.75 %, 11.22 %, and 7.52 % for bare, with 0.1 mm and 0.2 mm resin coating, respectively, and in-plane shear modulus was reduced by 10.87 %, 8.94 %, and 6.52 % for bare, with 0.1 mm and 0.2 mm resin coating conditions as compared to as-received (without ATF exposure) specimens. SEM micrographs and results too showed that properties were reduced and indicated that the glass/epoxy composite was resistive to fuel ingression. It was observed that bare specimens exhibited a reduction in shear properties due to ATF ingression to the polymeric network and induced internal stresses, which not only degraded the matrix and fiber-matrix adherence but created micro-cracks too in the resin at interfaces. Resin-coated specimens limit fuel ingression, which has led to a reduction in properties.